2020
DOI: 10.3390/catal10060658
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Interaction of Cerium and Barium-New Insight into the Promotion Effect in Cobalt Systems for Ammonia Synthesis

Abstract: This study explains a co-promoting interaction of cerium and barium additives in a cobalt catalyst used for ammonia synthesis. The results show that a synergistic effect of Ce and Ba promoters in the catalyst is associated with an emergence of a third promoter—BaCeO3—which forms in situ from its individual components during catalyst activation. The influence of perovskite-type barium cerate is substantial due to its strong basic properties, i.e. high electron-donating ability and a tendency to stabilize the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 56 publications
1
27
0
Order By: Relevance
“…It is also important to acknowledge that when both cerium and barium promoters are present in the system at the same time it leads to occurrence of synergistic effect between them. [26,38] This effect manifests itself with the activity increase greater then sum of the effect of individual promoters. This added effect is attributed to in-situ formation of third promoter combining cerium and barium elements -BaCeO 3 perovskite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to acknowledge that when both cerium and barium promoters are present in the system at the same time it leads to occurrence of synergistic effect between them. [26,38] This effect manifests itself with the activity increase greater then sum of the effect of individual promoters. This added effect is attributed to in-situ formation of third promoter combining cerium and barium elements -BaCeO 3 perovskite.…”
Section: Discussionmentioning
confidence: 99%
“…[35,36] It was proven that combination of those two types of promoters synergises and yields catalysts with activity greater than resulting from individual dopant action. [37,38] Unsupported cobalt catalysts display industrial application potential, [26,39] and on a large scale may be obtained through co-precipitation of cobalt and cerium hydroxycarbonates blend. The material is then thermally decomposed leading to formation of a Co 3 O 4 À CeO 2 mixture.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, during catalyst activation prior to the catalytic tests, the Co 3 O 4 is reduced to metallic cobalt. It has been previously observed that the addition of Ce stabilizes the hcp phase up to the temperature of 600 °C, [32][33][34] even though the allotropic transformation from hcp to fcc phase occur at 420 °C. 33,35 No significant change in the XRD is observed after the activity measurements ( Figure S2 and S3) compared to the structure of the samples after the activation treatment ( Figure 2), already anticipating the stability of the structure and of the catalytic properties of the materials.…”
Section: Catalysts Structural Characterizationmentioning
confidence: 99%
“…It has been previously observed that the addition of Ce stabilizes the hcp phase up to the temperature of 600 °C, [32][33][34] even though the allotropic transformation from hcp to fcc phase occur at 420 °C. 33,35 No significant change in the XRD is observed after the activity measurements ( Figure S2 and S3) compared to the structure of the samples after the activation treatment ( Figure 2), already anticipating the stability of the structure and of the catalytic properties of the materials. The reducibility of cobalt oxide to metallic Co, occurring during the activation treatment under hydrogen atmosphere at 500 °C, was investigated by temperature programmed reduction (H 2 -TPR), in order to understand the influence of cerium and barium.…”
Section: Catalysts Structural Characterizationmentioning
confidence: 99%
See 1 more Smart Citation